Topological volumes of fibrations: a note on open covers. Issue 5 (October 2022) - Löh, Clara; Moraschini, Marco
Abstract : We establish a straightforward estimate for the number of open sets with fundamental group constraints needed to cover the total space of fibrations. This leads to vanishing results for simplicial volume and minimal volume entropy, e.g., for certain mapping tori.